LpxT-Dependent Phosphorylation of Lipid A in Escherichia coli Increases Resistance to Deoxycholate and Enhances Gut Colonization - Tian, Xudong; Manat, Guillaume; Gasiorowski, Elise; Auger, Rodolphe; Hicham, Samia; Mengin-Lecreulx, Dominique; Boneca, Ivo Gomperts; Touzé, Thierry (Frontiers in Microbiology, 2021)
The cell surface of Gram-negative bacteria usually exhibits a net negative charge mostly conferred by lipopolysaccharides (LPS). This property sensitizes bacterial cells to cationic antimicrobial peptides, such as polymyxin B, by favoring their binding to the cell surface. Gram-negative bacteria can modify their surface to counteract these compounds such as the decoration of their LPS by positively charged groups. For example, in Escherichia coli and Salmonella, EptA and ArnT add amine-containing groups to the lipid A moiety. In contrast, LpxT enhances the net negative charge by catalyzing the synthesis of tri-phosphorylated lipid A, whose function is yet unknown. Here, we report that E. coli has the intrinsic ability to resist polymyxin B upon the simultaneous activation of the two component regulatory systems PhoPQ and PmrAB by intricate environmental cues. Among many LPS modifications, only EptA- and ArnT-dependent decorations were required for polymyxin B resistance. Conversely, the acquisition of polymyxin B resistance compromised the innate resistance of E. coli to deoxycholate, a major component of bile. The inhibition of LpxT by PmrR, under PmrAB-inducing conditions, specifically accounted for the acquired susceptibility to deoxycholate. We also report that the kinetics of intestinal colonization by the E.coli lpxT mutant was impaired as compared to wild-type in a mouse model of infection and that lpxT was upregulated at the temperature of the host. Together, these findings highlight an important function of LpxT and suggest that a tight equilibrium between EptA- and LpxT-dependent decorations, which occur at the same position of lipid A, is critical for the life style of E. coli.